Modern Techniques To Analyses Production Data (Journal of Chemical Engineering, 2014)
This paper shows a systematic & comprehensive demonstration of the methods available for analyzing production data, highlighting the advantages and limitations of each method. These methods comprise those techniques developed by Arps2, Fetkovich5, Blasingame2 and Agarwal-Gardner1 and a new method called Flowing Material Balance. Some methods yield recoverable reserves, while others give hydrocarbons-in-place. Traditional (Arps) decline analysis (exponential or hyperbolic) shows reasonable answers in many cases, but has its failings due to completely ignoring the flowing pressure data, one of the most important parameters. As a result, the reserves are underestimated or overestimated which are shown by tow examples. DOI: http://dx.doi.org/10.3329/jce.v27i2.17806 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 72-76